The rape of Poland : pattern of Soviet aggression : dedicated to the Polish people - Mikolajczyk, Stanislaw (New York : Whittlesey House, 1948)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: egodocumenten; Wereldoorlog 2; buitenlandse politiek; communisme; Polen; Sovjet-Unie.